1999
DOI: 10.1111/j.1469-0691.1999.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal coagulase-negative staphylococcal catheter-related bacteremia documented by molecular identification and typing

Abstract: Coagulase-negative staphylococci (CNS) form part of the skin flora and commonly cause nosocomial bloodstream and catheter-related infections [l]. The increasing use of intravascular catheters and the high number of immunocompromised patients contribute to the importance of CNS as a cause of catheter-related infection. It is commonly assumed that catheter-related bloodstream infection arises from multiplication of a single infecting clone of CNS, whereas blood-culture contamination by skin flora is polyclonal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…The results of the in vivo experiments prove the possibility of genetic variability in vivo in the context of a foreign body-associated infection. This report is therefore different from the other reports in which a coinfection with multiple unrelated clones was proposed [9,10].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The results of the in vivo experiments prove the possibility of genetic variability in vivo in the context of a foreign body-associated infection. This report is therefore different from the other reports in which a coinfection with multiple unrelated clones was proposed [9,10].…”
Section: Discussioncontrasting
confidence: 82%
“…colonizing the foreign bodies [9,10]. Another investigator suggested that phenotypic and genotypic variation among Staphylococcus epidermidis strains that infected joint prostheses may have resulted from changes that occurred in situ during the infection process [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, reports of polymicrobial and polyclonal outbreaks are increasing (7,25) due to staphylococci and Gram negative bacilli (14,29).…”
Section: Introductionmentioning
confidence: 99%
“…Although this assumption is supported by various clinical and microbiologic studies (8,15), there might be rare exceptions, with classification of strains as identical being the result of repeated contamination and of distinct strains being the result of a polyclonal infection (7,19). In addition, CoNS colonies were selected from primary subcultures of positive blood cultures based on colony morphology and preliminary agar diffusion susceptibility results; agar plates were not searched systematically for the presence of different strain types as was performed in other studies (4,6).…”
mentioning
confidence: 98%